2003
DOI: 10.1130/g19622.1
|View full text |Cite
|
Sign up to set email alerts
|

Tropical view of Quaternary sequence stratigraphy: Siliciclastic accumulation on slopes east of the Great Barrier Reef since the Last Glacial Maximum

Abstract: Generic models of continental-margin evolution predict that siliciclastic fluxes to slopes should be maximal and minimal during major sea-level lowstands and transgressions, respectively. Here we document the opposite for the northeast Australian margin, the largest extant mixed siliciclastic-carbonate depositional system. Cores from slopes of this margin consistently contain siliciclastic-rich intervals, ϳ0.3-1 m thick, in the upper few meters. Radiocarbon dates of planktonic foraminifera show that this inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 27 publications
2
46
0
Order By: Relevance
“…Here, geological evidence suggests that these reef systems have coexisted with very high water turbidity for millennia. Throughout the Quaternary life cycles of the GBR with glacio-eustatic changes in sea level, carbonate production and early reef initiation occurred during periods of high coastal water turbidity, maintained by sediment supply and oceanographic processes (e.g., Dunbar andDickens 2003, Page et al 2003). Over geological timescales, reef development and water quality are inextricably linked, and on that fact we are in complete agreement with DF10.…”
supporting
confidence: 78%
“…Here, geological evidence suggests that these reef systems have coexisted with very high water turbidity for millennia. Throughout the Quaternary life cycles of the GBR with glacio-eustatic changes in sea level, carbonate production and early reef initiation occurred during periods of high coastal water turbidity, maintained by sediment supply and oceanographic processes (e.g., Dunbar andDickens 2003, Page et al 2003). Over geological timescales, reef development and water quality are inextricably linked, and on that fact we are in complete agreement with DF10.…”
supporting
confidence: 78%
“…Both regions experience summer monsoonal rains and the present sediment yield from the Burdekin River is estimated to be similar to that of the Fitzroy River (Neil et al, 2002;Furnas, 2003). Paleoclimate evidence from vegetation changes in northern Queensland suggests that precipitation was reduced during the glacials (Kershaw et al, 2007), but then increased during the transgression, especially between 11 and 7 ka BP (Kershaw, 1985;Page et al, 2003). This would have resulted in increased water and sediment discharge during the late transgression.…”
Section: Comparison With Other Regions Of Northeast Australiamentioning
confidence: 94%
“…1), suggest that lowstand shedding of terrigenous mud is responsible for a dilution of the carbonate content in glacial-aged sediments from slope cores (Kudrass, 1982;Troedson and Davies, 2001). However, recent detailed studies of the tropical carbonate/ siliciclastic system of the central Great Barrier Reef (GBR) province (15-18°S) have challenged the conventional reciprocal model (Dunbar et al, 2000;Page et al, 2003;Dunbar and Dickens, 2003a,b;Francis et al, 2007). Their results, from a series of well dated marine cores from the north Queensland margin (Fig.…”
mentioning
confidence: 94%
“…Past study in the Pandora Trough (nearby the GoP) has shown this similar property: Numerous siliciclastic turbidites were recorded in the LGM and Younger Dryas in the Pandora Trough, and extremely high accumulation rate was observed during 15,800-17,700 years . However, also nearby the GoP, some studies showed different flux features: Records of the siliciclastic fluxes from the Great Barrier Reef (GBR), Queensland Trough, and Ashmore Troughs were lower in lowstand periods and were higher during late transgression (Dunbar et al 2000;Page et al 2003;Carson et al 2008). Therefore, sedimentary responses to sea level change would vary from one margin to another due to Fig.…”
Section: Introductionmentioning
confidence: 99%